Diurnal variations in air temperatures along cold region tunnels: Field observation and analytical solution - Lijie Zhang; Yanhu Mu; Xiaoming Zhu; Zhaohui Yang; Jun Hu; Chengcheng Du; Xiangbing Kong (Cold Regions Science and Technology, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Ultra-stable IrRu-doped NiSe array for highly efficient alkaline overall water electrolysis - Liwen Bie; Qiang Wang; Ruofei Du; Changxiang Shao; Tiansheng Mu; Xiaodong Zhu; Jian Gao (Chemical Engineering Journal, 2026)

Quantifying potential ground-ice meltwater release and seasonal active-layer water-storage change using decade-long InSAR-derived ground deformation in the Qilian Mountains - Guanjun Wei; Hongyu Zhou; Guangrong Li; Hongwen Mu; Zhigang Du; Yu Li (Journal of Hydrology, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

A physics-guided and scene-adaptive water index for consistent surface water mapping across regions and seasons - Shanchuan Guo; Pengfei Tang; Zilong Xia; Haowei Mu; Xiaoquan Pan; Peng Zhang; Yu Chen; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Removal of acetaminophen and total nitrogen from secondary effluent via a UV/PAA-biofilter process: Efficiency, biofilm characteristics, and reaction mechanism - Kun’ao Du; Congwei Luo; Mingshan Yin; Ran Zou; Ning Guo; Yao Xu; Shiqi Bai; Xue Jiang; Xiaoxiang Cheng; Liping Qiu; Daoji Wu; Ruimin Mu (Environmental Research, 2026)

Achieving 9.11 GHz broadband microwave absorption in CeO₂/Sn@C composites via Sn doping and structural modulation - Yecheng Qiu; Hao Ma; Jinhua Du; Wei Li; Xiaolong Wang; Yizhe Tian; Xu Mu; Defang Duan; Yingnan Wang (Chemical Engineering Journal, 2026)

Vertical profile observation of chlorophyll a in the Norwegian Sea based on the spaceborne lidar ICESat-2 - Jue Huang; Tianwei Du; Yulei Mu; Jinzhi Zhang; Yilin Liu; Yue Ma (Journal of Oceanology and Limnology, 2026)

The transformation of Ca/Mg-silicate to Co/Ni/Fe-silicate in biomass carbon from gourd leaves for supercapacitors - Shaoqing Zhang; Xiang Ke; Tianming Lv; Jiqi Zheng; Yang Mu; Xuchun Wang; Miao Cui; Teng Du; Changgong Meng (Chemical Engineering Journal, 2026)

A systematic identification and characterization of long noncoding RNAs during abiotic stress in Medicago truncatula - Kanghua Du; Yingan Zhu; Weiyu Yan; Ting Gao; Wanfu Mu; Ziwei Zhao; Zhong Dan; Xiaolu Meng; Haoting Chen; Yan Zhao; Jie Zhang (Journal of Plant Physiology, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Enabling long-cycle-life high-voltage calcium metal batteries with fluorinated alkoxyborate-based CaNa hybrid electrolytes - Xinyue Li; Shuangshuang Cui; Bin Chen; Xiaoke Mu; Dechen Zeng; Hongkun Wang; Yang Wang; Bo Peng; Tianyu Zheng; Dianxing Ju; Aobing Du; Zhenyou Li; et al. (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

A R2R3-MYB, VwMYB1, regulates anthocyanin biosynthesis in pansy petal blotch via transcriptional activation of VwF3′5'H - Xinyu Ye; Xiaopei Zhu; Yudan Li; Yanke Hu; Jinyan Mu; Xiaohua Du; Huichao Liu (Plant Cell Reports, 2026)

Species-dependent growth rates regulate community biomass under long-term warming and wetting in alpine meadow on the Qinghai-Tibet Plateau - Mingming Shi; Cuicui Mu; Bingrong Zhou; Xiaodong Li; Yunqiao Ma; Mei Mu; Jinyue Song; Xinlong Du; Huakun Zhou (Plant and Soil, 2026)

Innovative Approaches to Combat Antimicrobial Resistance: A Review of Emerging Therapies and Technologies - Mujeeb Ur Rahman; Junaid Ali Shah; Muhammad Nadeem Khan; Hazrat Bilal; Daochen Zhu; Zongjun Du; Da-Shuai Mu (Probiotics and Antimicrobial Proteins, 2026)

The synergistic effect of algal-bacterial granular sludge in a sequencing batch reactor with tetracycline-containing synthetic livestock and poultry breeding wastewater - Yuanda Du; Shoubo Zhao; Yanan Gao; Yujie Yan; Yi Kong; Wenwen Meng; Xinru Lu; Shun Zheng; Haolin Mu; Xiaojing Chen; Qiang Kong (Journal of Environmental Management, 2026)

Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Molecular characteristics of water-soluble organic aerosols under pollution conditions in a coal resource-based city revealed by FT-ICR MS: a significant role of sulfur-containing compounds - Chao Zhang; Ziyong Guo; Qingyu Hu; Lin Qi; Yang Chen; Yufeng Zhao; Nan Pei; Wei Sun; Xiaodong Hu; Yuxiang Yang; Fengxian Liu; Ling Mu; et al. (Fuel, 2026)

Liver-specific SLC13A3 modulation alleviates MASLD by regulating NAD+ metabolism - Jiangxia Du; Minhui Shen; Yuan Mu; Shuoran Peng; Zhifei Xu; Xiaochun Yang; Bo Yang; Peihua Luo; Hao Yan; Qiaojun He (Molecular and Cellular Biochemistry, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Aridity controls on the dominance of soil mineral-associated and particulate organic carbon in the Qinghai-Tibet Plateau - Hebin Liu; Mei Mu; Cuicui Mu; Kun Li; Yuguo Wei; Pengsi Lei; Fumei Liu; Xinlong Du; Shijie Li; Jianyu Li (Global and Planetary Change, 2026)

Revealing the dynamic biological flow between eastern and western China from the perspective of ecological network - Haowei Mu; Shanchuan Guo; Kaixuan Pan; Bo Yuan; Zhou Fang; Xingang Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2026)

Asymmetric nanochannels for high sensitive detection of AFB1 - Xinrui Xu; Lingxiao Liu; Qianyu Yang; Bin Du; Bing Liu; Xihui Mu; Zhaoyang Tong (Chemical Engineering Journal, 2026)

Construction of smartphone-assisted electrochemical molecularly imprinted sensor based on magnetic MOF@COF as a novel platform for portable and sensitive detection of staphylococcal enterotoxin B - Wei Hu; Minghao Ma; Bin Du; Yikan Zhao; Jiang Wang; Bing Liu; Xihui Mu; Zhangyan Hu; Zhihao Yi; Zhaoyang Tong (Journal of Environmental Chemical Engineering, 2025)

Does ecological restoration really improve ecosystem stability? ——An empirical test based on the Minjiang River Basin of China - Hanchu Du; Jinman Wang; Jun Wang; Biao Liu; Jiayin Mu; Xiao Zhang (Ecological Engineering, 2025)

The oldest known Curvicubitidae (Hemiptera) from the Permian (Wuchiapingian) of Zhangshu City, Jiangxi Province, southern China - Qian-Qi Zhang; Lin Mu; Lei Zhang; Xu-Heng Du; Hai-Chun Zhang (Palaeoworld, 2025)

Transformation of chloroxylenol in real sewer sediments: Key adsorption sites and CYP450-catalyzed biodegradation - Xinhui Xia; Yujia Du; Huizhi Mu; Dan Li; Shuocheng Shao; Qingliang Zhao; Liangliang Wei (Journal of Hazardous Materials, 2025)

Laccase-mimicking chiral Cu-nanozymes for enantioselective catalysis of phenolic substrates - Qiaodan Du; Zhihao Mu; Dan Liang; Xinman Han; Yuan Zhao; Wei Ma (Journal of Hazardous Materials, 2025)

A novel pre-oxidation of ultrafiltration membrane fouling mitigation via ascorbic acid-activated hydrogen peroxide - Yao Xu; Congwei Luo; Mingshan Yin; Xiaoxiang Cheng; Xinyu Zhang; Yan Jin; Ruimin Mu; Jingtao Xu; Kun'ao Du; Xue Jiang; Shiqi Bai; Daoji Wu; et al. (Chemical Engineering Journal, 2025)

Isotopic signaling and environmental significance of cave waters in a heavily rocky desertification area - Ju Ni; Yurong Mu; Dayun Zhu; Jialu Wang; Yurong Han; Yingshan Zhao; Ning Yang; Juanfang Du (Applied Geochemistry, 2025)

Enhanced biodegradation of crude oil by phosphate-solubilizing bacteria Bacillus subtilis PSB-1: Overcoming soluble phosphorus deficiency - Xudong Wang; Zhuorong Du; Zhenzhen Li; Mei Liu; Jun Mu; Lijuan Feng; Zhi Chen; Qingguo Chen (Journal of Environmental Management, 2025)

A rapid bag-protected micro-solid-phase extraction of polychlorinated biphenyls based on dual-ligand hollow MOF: one-stone-three-birds strategy from KMnO4 - Xuemei Wang; Jiyun Chen; Jie Zhang; Fu Mu; Zhen Zhang; Rao Peng; Xinzhen Du; Xiaoquan Lu (Chemical Engineering Journal, 2025)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

Environmental occurrence, human exposure routes, toxicity, and risk assessments of medium-chain chlorinated paraffins (MCCPs): a comprehensive review - Zhi-Hong Yu; Ying-Wen Mu; Yan-Chao Du; Tao Zeng (Archives of Toxicology, 2025)

Study on freeze-thaw damage and mechanical properties of fractured rock mass grouting reinforcement in alpine region open-pit mines - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Miaomiao Bai; Shigui Du (International Journal of Rock Mechanics and Mining Sciences, 2025)

Shear Failure Mechanism of Fiber-Reinforced Concrete–Rock Interface Under Freeze–Thaw Conditions - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Shigui Du; Miaomiao Bai (Rock Mechanics and Rock Engineering, 2025)

FarmSeg_VLM: A farmland remote sensing image segmentation method considering vision-language alignment - Haiyang Wu; Weiliang Mu; Dandan Zhong; Zhuofei Du; Haifeng Li; Chao Tao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Could chloroxylenol be used as WBE biomarker in gravity sewers? Fates, behaviors and feasible conditions - Xinhui Xia; Huizhi Mu; Yujia Du; Shuocheng Shao; Yaqun Li; Dan Li; Qingliang Zhao; Liangliang Wei (Water Research, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

MoS2-intercalated montmorillonite nanostructure coupled with N-doped carbon-encapsulated CoMn bimetallic nanocage: A stability-enhancing strategy for peroxymonosulfate activation to pollutant degradation - Xudong Liu; Zhinan Xie; Min Li; Jiarong Mu; Weihong Wang; Chunfang Du; Yiguo Su (Journal of Environmental Chemical Engineering, 2025)

Immune restoration mechanism analysis of Akkermansia PROBIO in mice treated with cyclophosphamide through Re-balancing microbiota composition - Junpeng Zhang; Xin Ma; Wenjiao Du; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2025)

A Review on Development, Challenges, and Future Perspectives of Ensemble Forecast - Jing Chen; Yuejian Zhu; Wansuo Duan; Xiefei Zhi; Jinzhong Min; Xiaoli Li; Guo Deng; Huiling Yuan; Jie Feng; Jun Du; Qiaoping Li; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

Quantifying the anthropogenic sensitivity of ecological patterns in arid urban agglomeration - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Chunqiang Li; Peijun Du (Applied Geography, 2025)

Enhanced treatment efficiency of moxifloxacin-containing domestic wastewater in sequence batch reactors coupled with Spartina alterniflora biochar - Yuan-da Du; Yanan Gao; Mengyu Qin; Jian Liu; Shoubo Zhao; Haolin Mu; Xinru Lu; Shun Zheng; Xiaojing Chen; Zishu Wu; Qiang Kong; Jian Zhang (Journal of Water Process Engineering, 2025)

Nutrient and stoichiometric characteristics of various organs in three typical desert plants from extreme desert ecosystems - Yi Du; Yulin Zhang; Zhihao Zhang; Yanju Gao; Zhaobin Mu; Waqar Islam; Fanjiang Zeng (Rhizosphere, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Molecular level simulation and analysis of removal of sulfur, nitrogen and carbon residue in residual oil hydrotreating process - Xinglong Qin; Ye Ji; Guangqing Cai; Tiansheng Wang; Yu Du; Guangyu Mu; Jian Zhang; Xuezhi Duan; Xin Pu; Xin Han; Lei Ye; Jichang Liu (Chemical Engineering Journal, 2025)

Design and experiment of a soil organic matter sensor-based variable-rate seeding control system for maize - Zhaohui Du; Li Yang; Dongxing Zhang; Tao Cui; Xiantao He; Chunji Xie; Yeyuan Jiang; Xiaoshuang Zhang; Jinsheng Mu; Haoyu Wang; Tianpu Xiao; Hongsheng Li (Computers and Electronics in Agriculture, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Effect of microplastics concentration and size on pollutants removal and antibiotic resistance genes (ARGs) generation in constructed wetlands: A metagenomics insight - Lin Liang; Weiliang Pan; Merui Mu; Lin Zhang; Xiangyu Yang; Ruina Zhang; Lianfeng Du; Xuan Guo (Journal of Hazardous Materials, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

Regionally adapted conservation tillage reduces the risk of crop yield losses: A global meta-analysis - Jun Sun; Wenquan Niu; Yadan Du; Li Ma; Siying Huang; Fei Mu; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

Comparison of primary and secondary metabolites and antioxidant activities by solid-state fermentation of Apios americana Medikus with different fungi - Hee Yul Lee; Hyo Seon Kim; Min Ju Kim; Young Hye Seo; Du Yong Cho; Ji Ho Lee; Ga Young Lee; Jong Bin Jeong; Mu Yeun Jang; Jin Hwan Lee; Jun Lee; Kye Man Cho (Food Chemistry, 2024)

The relationships between flavor substances and microbial communities during the fermentation of Chinese traditional red sour soup - Xin Zhang; Zhenyu Wang; Xianbing Xu; Xin Mu; Baifeng Fu; Jinxiu Xu; Shuhong Ye; Ming Du (Food Bioscience, 2024)

Quantifying the drought sensitivity of vegetation types in northern China from 1982 to 2022 - Bo Yuan; Shanchuan Guo; Xingang Zhang; Haowei Mu; Shengpeng Cao; Zilong Xia; Xiaoquan Pan; Peijun Du (Agricultural and Forest Meteorology, 2024)

Depth-dependent responses of soil bacterial communities to salinity in an arid region - Xinping Dong; Zhihao Zhang; Yan Lu; Li Li; Yi Du; Akash Tariq; Yanju Gao; Zhaobin Mu; Yuhe Zhu; Weiqi Wang; Jordi Sardans; Josep Peñuelas; et al. (Science of The Total Environment, 2024)

Balancing photovoltaic development and cropland protection: Assessing agrivoltaic potential in China - Zilong Xia; Yingjie Li; Shanchuan Guo; Nan Jia; Xiaoquan Pan; Haowei Mu; Ruishan Chen; Meiyu Guo; Peijun Du (Sustainable Production and Consumption, 2024)

Enhancement of non-glycoside phytoestrogens and digestive enzymatic inhibition activity during bioprocessing of isoflavone-enriched soybean leaves by mycelia of Tricholoma matsutake - Hee Yul Lee; Du Yong Cho; Jin Hwan Lee; Jihyun Lee; Jong Bin Jeong; Ji Ho Lee; Ga Young Lee; Mu Yeon Jang; Kye Man Cho (Food Bioscience, 2024)

Modeling Rip Current Systems around Multiple Submerged Breakwaters - Jie Xu; Yuchuan Wang; Baoying Mu; Huan Du; Yanlei Li; Zaijin You; Sheng Yan; Lixin Lu (Journal of Marine Science and Engineering, 2024)
Multiple submerged breakwaters (MSBWs) are commonly used coastal protection structures due to their specific advantages over the emerged ones. Rip currents, as the inevitable natural hazard in the gaps of these constructions, are investigated numerically in the present study. A fully nonlinear mild-slope equation (NMSE) model possessing both fully nonlinear and fully dispersive properties is validated and adopted in the simulations. With four monochromatic wave conditions of different wave heights, periods and incidences representing low-energy, typical, storm and oblique waves tested, the flow patterns and the low-frequency oscillations of the rip currents are studied. For the convenience of risk assessment, the rip risk level is divided into three degrees according to the maximum rip flow speed. The effects of the configurations of the MSBWs on the rip current system as well as the rip risk level are examined, considering different breakwater widths, heights, forms, gap widths and gap numbers. Simulation results suggest that the cross-shore configurations of MSBWs influence the rip risk level by inducing different wave energy dissipations but the longshore configurations of MSBWs by changing flow field patterns.

Continuous flow hydrothermal synthesis of MoVNbTeOx in micro-coil tubular reactor for oxidative dehydrogenation of ethane - Yuxin Chen; Yuting Wu; Shuairen Qian; Zhengwen Li; Changyan Xu; Ruiqi Du; Yao Mu; Tianying Dai; Binhang Yan; Yi Cheng (Chemical Engineering Journal, 2024)

Recent advances of 3-fucosyllactose in health effects and production - Zhihui Du; Zeyu Li; Cuie Guang; Yingying Zhu; Wanmeng Mu (Archives of Microbiology, 2024)

Preparation, taste characterization, and evaluation of oyster composite products with increased umami and salty - Baifeng Fu; Shuzhen Cheng; Xin Zhang; Junjie Yi; Zhishen Mu; Ming Du (Food Bioscience, 2024)

Distinct electrochemical and metabolic responses of anode respiring bacteria to sulfamethoxazole in microbial fuel cells coupled with constructed wetlands - Ruimin Mu; Xiuhan Liu; Yunfei Li; Feiyong Chen; Yalan Shi; Jin Wang; Xue Shen; Linxu Xu; Yufeng Du; Zhigang Yang (Bioresource Technology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Marinobacter sediminicola sp. nov. and Marinobacter xiaoshiensis sp. nov., Isolated from Coastal Sediment - Jing An; Run-Yuan Mao; Shu-Xin Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Current Microbiology, 2024)

Enhancing the Stability of Small Rescue Boats: A Study on the Necessity and Impact of Hydraulic Interconnected Suspensions - Xiaochun Mu; Hongwang Du; Wenchao Wang; Wei Xiong (Journal of Marine Science and Engineering, 2024)
Aiming to solve the problem that existing small rescue boats cannot realize the effective and stable rescue of human lives under high sea turbulence conditions, this paper proposes a parallel decoupled hydraulic interconnected suspension system for actual sea state. The system dynamics model is established, and its damping characteristics are analyzed by joint simulation. The results show that compared with the truss-type rescue ship, the suspension system can improve the transverse rocking resistance by 81.5% and the longitudinal rocking resistance by 25.0%, and the system has excellent transverse rocking resistance.

Degradation of the chiral fungicide penthiopyrad by six bacteria strains isolated from soils and the potential stereoselectivity - Jinming Chang; Li Dou; Shiyin Mu; Du Chi; Jing Shi; Kankan Zhang (Journal of Environmental Chemical Engineering, 2024)

Efficient production of 3-fucosyllactose in a plasmid-free engineered Escherichia coli through strengthening of the GDP-fucose pathway - Yihan Chen; Yingying Zhu; Hao Wang; Roulin Chen; Zhihui Du; Wanmeng Mu (Food Bioscience, 2024)

Efficient Cr(VI) remediation by electrospun composite porous nanofibers incorporating biomass with metal oxides and metal-organic framework - Ronggang Luo; Ruiqi Li; Zhangzhi Zheng; Lianpeng Zhang; Linkun Xie; Chunhua Wu; Siqun Wang; Xijuan Chai; Nyuk Ling Ma; Mu. Naushad; Guanben Du; Kaimeng Xu (Environmental Pollution, 2024)

Optimized tillage can enhance crop tolerance to extreme weather events: Evidence from field experiments and meta-analysis - Jun Sun; Wenquan Niu; Fei Mu; Ruoyu Li; Yadan Du; Li Ma; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

A ratiometric fluorescence imprinted sensor based on N-CDs and metal–organic frameworks for visual smart detection of malathion - Lidong Yang; Wei Hu; Fubin Pei; Zhiwei Liu; Jiang Wang; Zhaoyang Tong; Xihui Mu; Bin Du; Mingzhu Xia; Fengyun Wang; Bing Liu (Food Chemistry, 2024)

Serum Copper/Zinc Ratio in Overweight and Obese Children: a Cross-Sectional Study - Mu Du; Mingfang Qiu; Ye Qian; Tianqi Wang; Xiaobo Chen (Biological Trace Element Research, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Depositional and diagenetic controls on hydrocarbon generation of mudstones through clay–organic matter interactions: A comparative study of the Dongpu Depression, Bohai Bay Basin, China - Jiazong Du; Jingong Cai; Xiang Zeng; Yunxian Zhang; Xiaoshui Mu; Xinyu Wang (Journal of Asian Earth Sciences, 2024)

Contrasting characteristics of continental and oceanic deep convective systems at different life stages from CloudSat observations - Jinming Ge; Xiaoyu Hu; Qingyu Mu; Bochun Liu; Zeen Zhu; Jiajing Du; Jing Su; Qinghao Li; Chi Zhang (Atmospheric Research, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Quantifying landscape connectivity gaps between protected area and natural habitat - Haowei Mu; Shanchuan Guo; Xuecao Li; Yuyu Zhou; Yihe Lü; Xiaoping Du; Jianxi Huang; Chaode Ma; Xingang Zhang; Zilong Xia; Hong Fang; Peijun Du (Journal of Cleaner Production, 2024)

Response of runoff-sediment processes to vegetation restoration patterns under different rainfall regimes on the Loess Plateau - Xiaoxue Guo; Min Du; Peng Gao; Peng Tian; Guangju Zhao; Xingmin Mu; Ren Geng (CATENA, 2024)

Flexible bioimpedance-based dynamic monitoring of stress levels in live oysters - Luwei Zhang; You Li; Jiacheng Du; Boyu Mu; Jinyou Hu; Xiaoshuan Zhang (Aquaculture, 2023)

Genome-Wide Identification of MYB Family Genes in Cerasus humilis Reveals Candidate Genes Involved in Flavonoid Biosynthesis - Xiaofang Xue; Hongbo Fu; Xiwen Guo; Jiancheng Zhang; Pengfei Wang; Xiaopeng Mu; Shuai Zhang; Junjie Du (Plant Molecular Biology Reporter, 2023)

Fibrillarin promotes homologous recombination repair by facilitating the recruitment of recombinase RAD51 to DNA damage sites - Yanhua Mu; Jinhua Han; Mingjie Wu; Zongfang Li; Ke Du; Yameng Wei; Mengjie Wu; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

pH-dependent bisphenol A transformation and iodine disinfection byproduct generation by peracetic acid: Kinetic and mechanistic explorations - Shurun Yang; Yongli He; Zhechao Hua; Zhihui Xie; Chuan-Shu He; Zhaokun Xiong; Ye Du; Yang Liu; Guowei Xing; Jingyun Fang; Yang Mu; Bo Lai (Water Research, 2023)

The number and position of unsaturated bonds in aliphatic aldehydes affect the cysteine-glucose Maillard reaction: Formation mechanism and comparison of volatile compounds - Wenbin Du; Yutang Wang; Qinghong Yan; Shuang Bai; Yatao Huang; Long Li; Yuwen Mu; Ashbala Shakoor; Bei Fan; Fengzhong Wang (Food Research International, 2023)

Bioavailability-based risk assessment of various heavy metals via multi-exposure routes for children and teenagers in Beijing, China - Zhongwen Du; Zuguang Tian; Yelan Yin; Junxiao Wei; Yue Mu; Jianjun Cai; Zefeng Song; Kuang Cen (Environmental Science and Pollution Research, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Characterization of Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov., revealing the potential nitrogen fixation capacity of the order Marinilabiliales - Wen-Xing Yu; Qi-Yun Liang; Zong-Jun Du; Da-Shuai Mu (Frontiers in Marine Science, 2023)
Biological nitrogen fixation plays a crucial role in the marine nitrogen cycle, impacting global marine productivity and related carbon fluxes. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences.These two strains were isolated from the coastal sediment at Xiaoshi Island in Weihai, China. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences. It was revealed that strains D04 T and AAT T contain a set of nif gene clusters responsible for nitrogen fixation. Cell are yellow-colored, Gram-stain-negative, facultatively anaerobic, and rod-shaped bacteria. The optimal growth conditions for strain D04 T were found to be at 33 °C, pH 7.0, and in 2% (w/v) NaCl, while strain AAT T prefers growth conditions at 33 °C, pH 6.5, and in 3% (w/v) NaCl. The highest similarity of strains D04 T and AAT T was to Saccharicrinis fermentans NBRC 15936 T , with a similarity of 94.1% and 94.8%, respectively. The 16S rRNA gene sequence similarity between the two strains was 96.6%. These novel strains were found to represent new taxa of the Marinilabiliaceae family, and we propose the names Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov. with type strains D04 T (MCCC 1H00493 T = KCTC 92026 T ) and AAT T (MCCC 1H00485 T = KCTC 92028 T ), respectively. In this study, nitrogen fixation genes were predicted for 53 strains from the whole order Marinilabiliales and it was found that nitrogen fixation gene clusters were present in 26 strains. These gene clusters were found in every family in the order, highlighting that the presence of nitrogen-fixing gene clusters in the order is common. Nitrogen-fixing bacteria in sediments play an important role in various biogeochemical cycles. Thus, understanding the oceanic nitrogen cycle can provide insights into the energy flow of marine systems.

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Comparative genomics reveal distinct potential of Tamlana sp. S12 for algal polysaccharide degradation - Hai-Feng Xia; Xiao-Yu Jia; Yan-Xia Zhou; Zong-Jun Du; Da-Shuai Mu; Guan-Jun Chen (Frontiers in Marine Science, 2023)
Introduction Macroalgae contain various polysaccharides that serve as nutrient sources Introduction: Macroalgae contain various polysaccharides that serve as nutrient sources for marine bacteria. Carbohydrate-active enzymes (CAZymes) are the primary feature of marine bacteria that utilize these polysaccharides. In this study, we describe Tamlana sp. S12, a novel strain of marine flavobacteria that can degrade alginate and Laminaria japonica biomass, isolated from the intestines of the sea cucumber Apostichopus japonicas collected at Weihai coast. Methods We sequenced the entire genome of strain S12 and constructed a phylogenetic tree using the core genome sequences of related strains. We determined the enzymatic activity of strain S12 using the DNS method and measured its growth curve under different carbon sources using spectrophotometry. Results Strain S12 degraded dehydrated L. japonica fragments as the sole nutrient source within 48h. Strain S12 harbors a diverse array of CAZymes at multiple polysaccharide utilization loci (PUL). One PUL encoding lyases from PL6, 7, and 17 families may be used for the degradation of alginate. Additionally, strain S12 harbors PULs encoding carrageenan- and agar-targeting CAZymes. Comparative analysis with related flavobacteria from Algibacter , Maribacter , and Zobellia showed shared CAZymes among these strains, potentially derived from a common ancestor and stably maintained within strains. Genomic signatures, algal degradation ability, and CAZyme patterns suggest that strain S12 has the potential to degrade complex algal polysaccharides. Conclusion These results expand our knowledge of CAZymes and enrich our understanding of how marine Flavobacteriaceae adapt to marine algal polysaccharide environments. The availability of the genome of Tamlana sp. S12 will be beneficial for further analyses of marine Flavobacteriaceae.

Evaluation of local wheat (Triticum aestivum L.) germplasm resources and mining of excellent drought resistance loci in Shanxi province - Menglin Lei; Xia Liu; Yanzhen Wang; Xiaojun Zhang; Huiling Du; Zhixin Mu (Genetic Resources and Crop Evolution, 2023)

Failure mechanism and movement process of three loess landslides due to freeze-thaw cycle in the Fangtai village, Yongjing County, Chinese Loess Plateau - Jiaxu Kong; Jianqi Zhuang; Jianbing Peng; Penghui Ma; Jiewei Zhan; Jiaqi Mu; Jie Wang; Dan Zhang; Jia Zheng; Yuting Fu; Shibao Wang; Chenhui Du (Engineering Geology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Comparative analyses of five complete chloroplast genomes from the endemic genus Cremanthodium (Asteraceae) in Himalayan and adjacent areas - Weihong Zhong; Xiaolang Du; Xiaoyun Wang; Lan Cao; Zejing Mu; Guoyue Zhong (Physiology and Molecular Biology of Plants, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Structural characteristics and disruption ripple effect in a meso-level electric vehicle Lithium-ion battery supply chain network - Dong Mu; Huanyu Ren; Chao Wang; Xiongping Yue; Jianbang Du; Pezhman Ghadimi (Resources Policy, 2023)

Collagen-anchored cascade nanoreactors with prolonged intratumoral retention for combined cancer starvation and chemotherapy - Jingqing Mu; Yuyuan Du; Xingwei Li; Ran Yan; Haiping Zhong; Maoyu Cai; Na Yu; Jinchao Zhang; Xiaoyong Yuan; Xia Hua; Shutao Guo (Chemical Engineering Journal, 2023)

Impact of repeated intravenous infusions of umbilical cord–derived versus bone marrow–derived mesenchymal stem cells on angiogenesis in a pregnant experimentally induced deep venous thrombosis rat model - Xi Cheng; Weina Wang; Rong Du; Mu Zhang; Yuanyuan Xie; Weiwei Sun; Jingjing Ji; Baolan Sun; Yuquan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

Predation capacity of Bradymonabacteria, a recently discovered group in the order Bradymonadales, isolated from marine sediments - Ya Gong; Xiu-Ya Ping; Chen-Hang Zeng; Shu-Xin Wang; Yi Zhou; Ming-Yi Wang; Da-Shuai Mu; Zong-Jun Du (Archives of Microbiology, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Genome-Wide Identification and Expression Analysis of AAAP Gene Family in Cerasus humilis During Fruit Development - Hongbo Fu; Pengfei Wang; Junjie Du; Xiaopeng Mu; Shengyong Yuan; Yongchao Yang; Jie Li (Plant Molecular Biology Reporter, 2022)

Expression Characteristics and Putative Functions of KIF3A/KIF3B During Spermiogenesis of Phascolosoma esculenta - Chen Du; Danli Mu; Xinming Gao; Shengyu Luo; Jianping Wang; Shan Jin; Junquan Zhu (Journal of Ocean University of China, 2022)

Psychroserpens luteolus sp. nov., isolated from Gelidium, reclassification of Ichthyenterobacterium magnum as Psychroserpens magnus comb. nov., Flavihalobacter algicola as Psychroserpens algicola comb. nov., Arcticiflavibacter luteus as Psychroserpens luteus comb. nov - Xiu-Ya Ping; Kai Wang; Jin-Yu Zhang; Shu-Xin Wang; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Description of Lujinxingia vulgaris sp. nov., isolated from coastal sediment via prey-traps - Shuo Wang; Da-Shuai Mu; Guang-Yu Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2021)

Strategies for culturing active/dormant marine microbes - Da-Shuai Mu; Yang Ouyang; Guan-Jun Chen; Zong-Jun Du (Marine Life Science & Technology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Effect of climate change induced extreme precipitation on landslide activity in the Three Gorges Reservoir, China - Dengfeng Zhu; Kun Song; Jingchao Mu; Haifeng Huang; Hongjian Du; Fanzhe Xiazhuang; Chi Sun (Bulletin of Engineering Geology and the Environment, 2021)

A global analysis of enemy release and its variation with latitude - Meng Xu; Xidong Mu; Shuang Zhang; Jaimie T. A. Dick; Bingtao Zhu; Dangen Gu; Yexin Yang; Du Luo; Yinchang Hu (Global Ecology and Biogeography, 2021)
Aim The enemy release hypothesis (ERH) posits that exotic species suffer less enemy damage than natives, which promotes their successful invasion. However, the generality of less damage for exotics remains widely debated. A recent view proposes that enemy release (ER) could change systematically with latitude, potentially helping to explain these inconsistencies. Here, we test whether exotic plant species suffer consistently lower herbivore damage relative to natives and whether ER varies with latitude. Location Global. Time period 1960–2018. Major taxa studied Plants. Methods Using leaf herbivory data for 1,098 plant species, we compared the herbivory rate between exotic and native plants across all taxa, between the introduced and native range of exotic species and between exotic and native species co‐occurring in the same community. We tested the interaction effect between origin (exotic versus native) and latitude to assess variation in ER with latitude. We also examined whether the effect of origin and its interaction with latitude changed with plant growth form (woody versus non‐woody). Finally, based on two ER effect‐size datasets, two meta‐regressions were performed to demonstrate the relationship between ER and latitude. Results Leaf herbivory rates were commonly lower for exotics than for natives. However, this differential herbivory rate was significant only for woody plants. No significant interactions were found between origin and latitude, indicating that ER did not change with latitude. The meta‐regressions also demonstrated that ER was not significantly correlated with latitude. Main conclusions The widespread lower herbivory rate for exotic compared with native woody plant species supports the ERH for exotic woody plants. Consistent ER with latitude indicates that ER should play a similar role regardless of latitude. One future challenge is to assess the extent to which ER in woody exotic plants translates to performance advantages and thereby influences their invasion success.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Growth and Photosynthetic Inhibition of Cerium Oxide Nanoparticles on Soybean (Glycine max) - Jinxing Li; Qili Mu; Yilin Du; Jipeng Luo; Yuankun Liu; Tingqiang Li (Bulletin of Environmental Contamination and Toxicology, 2020)

Decreased mRNA Expressions of CD40L in Patients with Neuromyelitis Optica Spectrum Disorder - Ziyan Shi; Ling Feng; Zhiyun Lian; Ju Liu; Hongxi Chen; Qin Du; Ying Zhang; Qin Zhang; Mu Yang; Hongyu Zhou (Journal of Molecular Neuroscience, 2020)

Molecular characterization of a novel fusarivirus infecting the plant-pathogenic fungus Botryosphaeria dothidea - Wenyi Liu; Du Hai; Fan Mu; Xiaojing Yu; Yingtong Zhao; Bangling He; Jiatao Xie; Daohong Jiang; Huixiang Liu (Archives of Virology, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Molecular Characterization, Tissue Distribution and Localization of Larimichthys crocea Kif3a and Kif3b and Expression Analysis of Their Genes During Spermiogenesis - Danli Mu; Chen Du; Suyan Fu; Jingqian Wang; Congcong Hou; Daojun Tang; Junquan Zhu (Journal of Ocean University of China, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Association of polymorphisms of CYP11B2 gene –344C/T and ACE gene I/D with antihypertensive response to angiotensin receptor blockers in Chinese with hypertension - Hongtao Gong; Liying Mu; Tong Zhang; Xiuying Xu; Fenghe Du (Journal of Genetics, 2019)

Long non-coding RNA (lncRNA) MAGI2-AS3 inhibits breast cancer cell growth by targeting the Fas/FasL signalling pathway - Yong Yang; Hong Yang; Miao Xu; Haibin Zhang; Mingtao Sun; Peng Mu; Tongbao Dong; Shanmei Du; Kui Liu (Human Cell, 2018)

Cell regeneration and cyclic catalysis of engineered Kluyveromyces marxianus of a d-psicose-3-epimerase gene from Agrobacterium tumefaciens for d-allulose production - Peizhou Yang; Xingxing Zhu; Zhi Zheng; Dongdong Mu; Shaotong Jiang; Shuizhong Luo; Yun Wu; Minrui Du (World Journal of Microbiology and Biotechnology, 2018)

Seasonal Variation of CO2 Vertical Distribution in the Atmospheric Boundary Layer and Impact of Meteorological Parameters - Koorosh Esteki; Neeraj Prakash; Yanli Li; Chao Mu; Ke Du (International Journal of Environmental Research, 2017)

Tempo-spatial dynamics of water quality and its response to river flow in estuary of Taihu Lake based on GOCI imagery - Chenggong Du; Yunmei Li; Qiao Wang; Ge Liu; Zhubin Zheng; Meng Mu; Yuan Li (Environmental Science and Pollution Research, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

100 years of Sediment History of Heavy Metals in Daya Bay, China - J. Z. Du; H. D. Mu; H. Q. Song; S. P. Yan; Y. J. Gu; J. Zhang (Water, Air, & Soil Pollution, 2008)